Why PPP exchange rates should be avoided in global poverty estimates - Michail Moatsos (ZBW – Leibniz Information Centre for Economics, 2020)
Purchasing Power Parity (PPP) exchange rates work appreciatively for comparing economies across the globe, instead of the standard market exchange rates. PPPs come closer to represent the relative size of the economies because they correct for non-tradeables that are relatively cheaper in less developed countries. However, those rates are constructed for comparing countries, or their households, in sum. Thereby when they are used to compare sub-groups, e.g. the poor in each country, their methodological foundations are stretched beyond their specifications. This paper highlights the often neglected issues that are raised from this standard practice in global poverty measurement.
Keywords: I3; 330; Global Poverty; Absolute Poverty; PPP; Purchasing Power Parity; Poverty Measurement; Global Poverty Measurement